Zwitterions fine-tune interactions in electrolyte solutions (data) - Perkin, S (University of Oxford, 2022)
This dataset comprises the measurements presented in manuscript entitled "Zwitterions fine-tune interactions in electrolyte solutions". F/R and D are presented for each salt and zwitterion concentration as described in the manuscript.